Efficient storage codes for non-volatile memories - Chua, Melissa Wan Jun (2016)
The onset of the mobile age and the rapid growth of the mobile technology have initiated a tremendous demand for high density storage and retrieval of huge amount of data. The conventional magnetic recording systems are expected to reach storage density limits. In the recent years, the non-volatile memory (NVM) systems have shown a high potential for future ultra-high density data storage systems. Compared with magnetic recording systems, the NVM systems have numerous attractive features, which include lower power consumption, faster read access time, better mechanical reliability, compactness and shock resistance. Flash memory is currently the most mature storage medium in portable electronic devices and is rapidly being introduced into mobile gadgets and data-intensive computer systems. Current semiconductor market researches has revealed that non-volatile memory devices based in flash technology will reach sales in the order of $26 billion by end of 2010 and $51.2 billion in 2015 [1]. Due to the maturity ofFlash technology, it is proposed to set the benchmark for other emerging NVM technologies. The trend of consumer electronics indicates that constant growing demand for an increase in data storage capacity. Examples are the megapixel race in consumer digital cameras. As an example, the Apple QuickTake 100 launched by Apple in 1994 contained an image sensor with only 0.3 megapixels [2], nowadays cameras like Sony, possess a sensor with a resolution 24.6 megapixels [3]. In the same trend, digital video systems have increased resolution due to the new high definition HD video standards. All these new technologies require a higher amount of storage capacity in order to accommodate their media content, as a result, an increment in the demand for higher capacity non-volatile memories is highly expected. The increasing market demand for high capacities non-volatile memory devices serves as a driving force to incentivize recent outgoing research in the non-volatile field. Nevertheless, the physical constraints of Flash makes additional scaling a tremendously expensive task, therefore we exploit alternative technology to break through what the Flash technology has to offer. The phase-change random access memory (PCRAM) is one of the most promising alternative technologies for NVM and is one of the promising candidates to replace Flash. It is envisage that Phase Change Memory (PCM) technology will eventually become a mainstream NVM technology. Hence development o f coding techniques for PCM is focused in this work. While the technological innovations in the design and development of storage media and system are key to achieving high capacity storage systems, the role of advanced coding techniques is increasingly becoming crucial as a cost-effective means of improving density. Despite the favoured position of NVM in the mobile sector, there are poor reliability concerns related to such memories. These poor reliability issues were contributed from resistance drift over time, cells that are stuck in a particular state and inter-cell coupling. This dissertation applies variants of data storage codes to combat some of these reliability issues. Specifically, the core of the work is focused on two sets of issues - asymmetric errors caused by a shift in the cell’s resistance over time and the failure contributed from the limitation of the maximum number of rewriting operations of a PCM cell. Write-once Memory (WOM)-codes were proposed as an efficient storage codes in extending the lifetime of PCM cells, by minimizing the number of memory degrading reset cycles. An efficient code construction method is briefly described before a critical criterion is proposed to design WOM-codes with high rates. From the WOM-rate analysis, the WOM-codes designed have an improvement of 2% for the unrestricted codes and 1% for the restricted codes. Subsequently, a novel construction method is proposed to achieve high rate non-binary WOM-codes that have a shorter codeword length compared to the best known WOM-codes. Achieving high WOM-rates with shorter codeword length is beneficial as coding efficiency is maximized with less complex encoding and decoding operations. A newly designed two-write 4-ary WOM-code, which is proposed in this work achieves an improvement in coding efficiency of O.2%. Next, the work is focused on proposing solutions to combat asymmetric errors. A novel scheme known as rank modulation (RM) was recently proposed for this purpose. As these codes are currently encoded and decoded based on a look-up table (LUT), a novel enumerative coding scheme is proposed. The enumerative coding scheme proposes to compute the lexicographic index analytically rather than adopting a brute-force enumeration technique. This results in a desirable reduction in encoding and decoding complexity. Additionally, a hybrid RM scheme is proposed with the motivation of providing a method of constructing WOM-codes without having to sacrifice as much code rate as the state-of-the-art RM codes, and yet able to provide better performance.